2020
DOI: 10.1007/s10750-020-04353-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton in extreme environments: importance and consequences of habitat permanency

Abstract: There is hardly any sunshine exposed surface on this Earth, be it water or terrain, which would not support some biota. Still, many habitats offer harsh conditions requiring specialized physiological adaptations to survive. These environments are referred to as extremes; often inhabited by extremophilic organisms. In this review, characteristic species and assemblage properties of phytoplankton inhabiting extreme environments (especially lakes and pools where planktic life is potentially possible and independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 179 publications
(178 reference statements)
0
28
0
3
Order By: Relevance
“…Terrestrial algae, abundant in both extreme and temperate environments, are exposed to several abiotic stressors related to their habitat outside the aquatic environment such as UV radiation, freezing, and unpredictable water availability, where periods of drought of several weeks or even months punctuated by rains are common [ 1 , 2 , 3 ]. The subsequent success of terrestrial algae is partly due to their ability to withstand the stress of undergoing repeated and extended drying–rewetting cycles [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial algae, abundant in both extreme and temperate environments, are exposed to several abiotic stressors related to their habitat outside the aquatic environment such as UV radiation, freezing, and unpredictable water availability, where periods of drought of several weeks or even months punctuated by rains are common [ 1 , 2 , 3 ]. The subsequent success of terrestrial algae is partly due to their ability to withstand the stress of undergoing repeated and extended drying–rewetting cycles [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The green unicellular algae Dunaliella salina and D. parva are usually the most frequently observed hypersaline planktonic species, occurring over a wide salt range from 9 to 250 g/l (Esmaeili Dahesht et al ., 2010; Oren, 2020). Interestingly, eco‐physiological experiments showed that Dunaliella growth optima are lower (up to 90–150 g/l) than the salinity range of their occurrence in nature, indicating plastic responses to changes in salinity levels (Padisák & Naselli‐Flores, 2021) and also potentially due to relaxation of trophic pressures as has been suggested for invertebrates (Arribas et al ., 2019). As a result, a wide spectrum of abundances of Dunaliella were recorded across hypersaline waters in different regions: up to 1 × 10 10 cells/m 3 in Mexican saltern ponds (Olmos et al ., 2009), 5 × 10 9 cells/m 3 in Greek salterns (Dolapsakis et al ., 2005), 4 × 10 10 cells/m 3 in the Dead Sea (Oren et al ., 1995), 7 × 10 7 cells/m 3 at Lake Tyrell (Australia) (Heidelberg et al ., 2013) and up to more than 50 × 10 7 cells/m 3 in Crimean saline lakes (Senicheva et al ., 2008).…”
Section: Hypersaline Biota: Diversity Adaptations and Metabolismsmentioning
confidence: 95%
“…Arthrospira and Limnospira species are well known for their applications ranging from food supplements to industrial polymers ( 2 4 ). The East African Rift Valley Region contains a number of saline lakes that are among the most productive ecosystems in the world ( 5 , 6 ), albeit with very few studies being done there ( 6 , 7 ). As a part of our investigations on identifying the genomes of potentially industrial halophiles constituting part of the Big Momela microbiome, we report here the first draft genome sequence of a Limnospira species from that ecosystem.…”
Section: Announcementmentioning
confidence: 99%